Probability Model Quality of Informations Systems - Kalnius, R.; Eidukas, D. (Elektronika ir Elektrotechnika, 2009)
This publication is about continuous between-operational control main probabilities characteristics modeling techniques for multilevel IS, when separate independent parameters defect level probabilities distributions are set (known) in chosen control schematics place. Denied IS streams go back to production process for regeneration and classification rules, in different control levels, are similar when IS classification first and second type errors are not denied by different parameters (good is denied or bad is accepted as good). Made IS defect level probability density direct and reverse transformations models by separate parameter levels densities transformations. Offered to use approximated models instead of exact whole IS defect level probabilities density transformed models because of complicated process of integration and models get more simple expressions. Ill. 6, bibl. 11 (in English; abstracts in English, Russian and Lithuanian).